PERAN GURU DALAM MELESTARIKAN BAHASA DAERAH MELALUI PEMBELAJARAN DISEKOLAH DASAR NEGERI 011 SANGATTA UTARA - hidayati, lily; latifah, jauhar; lisa lia, anggun (Prodi PGMI IAI Darul Ulum Kandangan, 2025)
This study aims to examine the role of teachers in preserving local languages through learning activities at SD 011 Sangatta Utara. Using a qualitative approach, data were collected through observation, interviews, and documentation. The results indicate that teachers play a strategic role as educators, mentors, and agents of cultural and linguistic preservation. Through methods such as dialogues, folk stories, pictures, and interactive games, teachers foster students’ interest in using local languages, particularly the Kutai language. The integration of local languages into learning activities, supported by technology and an understanding of students’ characteristics, enhances the effectiveness of preservation efforts. Moreover, teachers cultivate students’ pride and appreciation for their local culture, making them key figures in maintaining the sustainability of local languages amid modernization and globalization.